DAMPAK KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI RICHEESE CABANG GRAND DEPOK CITY - Hira, Rosa Janatul; Jullistia, Vriska Naya; Inayatuzzahra, Syifa; Cipta, Ramdhina; Fadillah, Nanda Nur; Susilowati, Isnurrini Hidayat (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2024)
The fast-food industry, particularly Richeese Factory, plays a significant role in the global culinary landscape. This study aims to evaluate the impact of service quality on customer satisfaction at Richeese Factory GDC using a combination of library and field research methods. The study employs a cross-sectional design, with data collected through questionnaires from 99 randomly selected respondents. Service quality was assessed based on aspects such as speed, order accuracy, staff friendliness, and restaurant cleanliness. Linear regression methods were applied, including instrument tests for validity, reliability, and classical assumptions such as normality, heteroscedasticity, and multicollinearity. The validity and reliability tests showed that the questionnaire was reliable and valid. The classical assumption tests indicated that the data distribution was not normal; however, the regression model did not show heteroscedasticity or multicollinearity. Correlation analysis demonstrated a strong and positive relationship between the two variables. The coefficient of determination revealed that 29.2% of customer satisfaction variability was influenced by service quality, with the regression equation Y = 24.180 + 0.449X, indicating a positive effect. The T-test also showed a positive and significant effect of service quality on customer satisfaction, with a t-value of 6.322, which is greater than the t-table value of 1.988. These findings highlight the importance of improving service quality to achieve optimal customer satisfaction in the fast-food industry.